A third MRX family (MRX68) is the result of mutation in the long chain fatty acid-CoA ligase 4 (FACL4) gene: proposal of a rapid enzymatic assay for screening mentally retarded patients. Issue 1 (1st January 2003) - Longo, I; Frints, S G M; Fryns, J-P; Meloni, I; Pescucci, C; Ariani, F; Borghgraef, M; Raynaud, M; Marynen, P; Schwartz, C; Renieri, A; Froyen, G
Abstract : Background: The gene encoding fatty acid CoA ligase 4 ( FACL4 ) is mutated in families with non-specific X linked mental retardation (MRX) and is responsible for cognitive impairment in the contiguous gene syndrome ATS-MR (Alport syndrome and mental retardation), mapped to Xq22.3. This finding makes this gene a good candidate for other mental retardation disorders mapping in this region. Methods: We have screened the FACL4 gene in eight families, two MRX and six syndromic X linked mental retardation (MRXS), mapping in a large interval encompassing Xq22.3. Results: We have found a missense mutation in MRX68. The mutation (c.1001C>T in the brain isoform) cosegregates with the disease and changes a highly conserved proline into a leucine (p.P375L) in the first luciferase domain, which markedly reduces the enzymatic activity. Furthermore, all heterozygous females showed completely skewed X inactivation in blood leucocytes, as happens in all reported females with other FACL4 point mutations or deletions. Conclusions: Since the FACL4 gene is highly expressed in brain, where it encodes a brain specific isoform, and is located in hippocampal and cerebellar neurones, a role for this gene in cognitive processes can be expected. Here we report the third MRX family with a FACL4 mutation and describe the development of a rapid enzymatic assay on peripheral blood that we propose as a sensitive, robust, and efficient diagnostic tool in mentally retarded males.